Enhancing Arabic Literacy in Islamic Boarding School: The Role and Pedagogical Implications of Interactive Whiteboard Technology - Hanifansyah, Nur; Baharun, Segaf; Solehudin, Muhamad; Arisandi, Yusuf; Mahmudah, Menik; Syakur, Sultan Abdus (Journal of Arabic Language Learning and Teaching (JALLT), 2025)
The integration of Interactive Whiteboard (IWB) technology into Arabic literacy instruction has drawn growing interest, particularly in pesantren (Islamic boarding schools), where traditional methods still prevail. Existing research largely addresses general or ESL contexts, leaving a gap in understanding IWB use in Islamic educational settings. This study explores the effectiveness of IWBs in enhancing Arabic reading proficiency, with a focus on student engagement, comprehension, and pedagogical outcomes. A mixed-methods approach was employed, involving 60 third-grade Tsanawiyah students at Pesantren Darullughah Wadda’wah. Using a quasi-experimental design, the study included pre- and post-tests, classroom observations, and interviews. Results show a significant improvement in reading skills, with post-test scores increasing by 24.4 percentage points (from 54.2 to 78.6; p < 0.01, d = 1.15). IWBs also promoted interactive learning and peer collaboration. Qualitative data supported these findings, highlighting enhanced student participation and classroom engagement. Despite positive outcomes, challenges such as insufficient teacher training and limited infrastructure were noted. The study contributes to the discourse on digital transformation in Arabic education and suggests that IWBs can effectively bridge traditional and modern pedagogical approaches in pesantren, offering a scalable model for improving literacy and learner interaction in Islamic educational contexts.